Changing Between Virtual Reality and Real-World Adversely Affects Memory Recall Accuracy - Lamers, Maarten H.; Lanen, Maik (Frontiers in Virtual Reality, 2021)
Context-dependency effects on memory exist, whereby people’s context influences their ability to accurately recall items from memory. This effect was not previously studied when considering virtual reality as an environmental context. We show that adverse effects on recall of memorized items exist when changing between virtual and real environments. The effect was not present when memorizing and recall were both done in VR; it appears to be caused by the change of environmental context. This previously unknown effect may impact how we use VR for memorization tasks, particularly when accurate recall of memorized information in a real environment is important. In a memory-recall experiment (n=51) participants that underwent a context change involving VR after memorizing performed significantly worse on 24-hour later item recall than those who did not change context (17% lower accuracy, p<0.001). In particular memorizing in VR as opposed to a real environment lowers accuracy of recall in a real environment (24% lower, p=0.001).